(untitled) (Studia Politica. Romanian Political Science Review, 2025)
The political left in Bulgaria experienced a deep crisis over the last eight years having lost mostly eighty percent of its electorate. The main left-wing party operated an ideological shift to a kind of left nationalism and conservative socialism, trying to recover its support. On the other side there are numerous NGOs, initiatives, media platforms and even think-tanks, small in size, scattered everywhere, which identify themselves as center-left, socially sensitive, feminist, anti-racist even anti-capitalist. Their ideologies seem to be close to the progressive European left. But often they work separately and quite are reserved towards the political left. The article explores the conditions, the opportunities, and the obstacles for a possible reconstruction of an influential and progressive left political actor in Bulgaria.